HUBUNGAN POLA ASUH ORANG TUA DENGAN MOTIVASI BELAJAR PESERTA DIDIK DI KELAS VIII SMP NEGERI 23 PADANG - Sandi, Fara Dilla; Kasih, Fitria; Yulastri, Weni (Bimbingan dan Konseling, 2014)
Parenting is one of factor affecting studentâs motivation. Provision of appropriate parenting should also followed the good motivation of students to study. But infact that students are lack of motivation. Therefore, it is necessary to having research on relationship of parenting with the sutdentâs motivation. This study were aimed to describe : (1) description of studentâs parenting. (2) description of studentâs learning motivation. (3) relationships of parenting with studentâs learning motivation in Class VIII SMPN 23 Padang. Type of research was quantitative descriptive correlational study with population of all the eighth grade students of SMP Negeri 23 Padang, total of 222 people. Sample were taken in proportional random sampling total of 56 samples people. Data were collected through questionnaire. Data were analyzed using percentage analytical technique, while hypothesis testing to see the relationship of parenting with studentâs motivation to study using Pearson Product Moment Correlation formula, the calculation using computer with Microsoft Excel and SPSS version 17.00. Results of data analysis : (1) description of parenting of students is in good category with percentage of 83.93 %. (2) description of motivation of students is in high category with percentage of 58.93 %. (3) relationship of parenting studentâs motivation obtained rcount 0,580 > and rtable 0.2632 at df 54 with significance level of 0.000 (sig < 0.05). So research result found that the relationship of parenting with studentâs motivate to study of eighth grade students of SMPN 23 Padang is a quite strong significant level.